Oldest allies, guarded friends : the United States and France since 1940 - Cogan, Charles 11.01.1928-14.12.2017 (Praeger, 1994)
Offering a revisionist-style look at the French-American relationship, Charles G. Cogan presents a series of case studies dating from the "great misunderstanding" between the Roosevelt administration and the Free French movement in World War II to the formation of the Euro-Corps in the early 1990s. In struggling to regain France's leading position in Europe, the French leadership under Charles de Gaulle sought on the one hand an independent nuclear force, and, on the other, a strengthening of Europe with a Franco-German alliance at its core. Both of these policies provoked friction with the United States; both will now have to be revised, the author asserts, after the end of the Cold War and the emergence of a powerful, reunited Germany. The overall prospect, however, is that of continuing differences between France and the United States, as the antagonisms of the past, which date primarily from the World War II era, will not easily die out. Written by a former senior intelligence officer with a background of extensive French government and academic relationships, Oldest Allies, Guarded Friends will be invaluable to all students of contemporary European history and U.S. foreign relations.